Interim estimates of 2017–18 seasonal influenza vaccine effectiveness — United States, February 2018. Issue 4 (30th March 2018) - Flannery, Brendan; Chung, Jessie R.; Belongia, Edward A.; McLean, Huong Q.; Gaglani, Manjusha; Murthy, Kempapura; Zimmerman, Richard K.; Nowalk, Mary Patricia; Jackson, Michael L.; Jackson, Lisa A.; Monto, Arnold S.; Martin, Emily T.; et al.
Abstract : This report documents the low effectiveness of this year's influenza vaccine, both in normal and immunosuppressed individuals.